1987
DOI: 10.1212/wnl.37.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease

Abstract: Carboxyl terminal alpha-amidation confers biologic activity to many neuropeptides. Levels of alpha-amidating activity, peptidyl-glycine alpha-amidating monooxygenase (PAM), were reduced in the CSF of patients with dementia of the Alzheimer type (DAT) compared with healthy, age-matched controls. Repeat lumbar puncture data revealed a decline in CSF PAM activity of approximately 16% per year in DAT patients. Of the cerebral cortical regions examined, only the temporal pole showed reduced PAM activity in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The imbalance of copper to CP in CSF indicates that CP is not the major copper sequestering protein in this compartment, suggesting that copper is bound to either low molecular weight compounds or to other copper-binding proteins. Several protein candidates may be proposed to bind copper in CSF, like peptidyl-glycine a-amidating monooxygenase (PAM) (Wand et al 1987), Cu, Zn superoxide dismutase (both SOD1 and SOD3) (Jacobsson et al 2001), the Ab polypeptide (Squitti et al 2006). One representative analysis is shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imbalance of copper to CP in CSF indicates that CP is not the major copper sequestering protein in this compartment, suggesting that copper is bound to either low molecular weight compounds or to other copper-binding proteins. Several protein candidates may be proposed to bind copper in CSF, like peptidyl-glycine a-amidating monooxygenase (PAM) (Wand et al 1987), Cu, Zn superoxide dismutase (both SOD1 and SOD3) (Jacobsson et al 2001), the Ab polypeptide (Squitti et al 2006). One representative analysis is shown.…”
Section: Discussionmentioning
confidence: 99%
“…Purified human ceruloplasmin (hCP) (45 ng) was used as standard However, due to their low amount in CSF (in the nM range or less), none of them can represent the major copper-binding protein element. Of note, the concentration of some copper-binding proteins such as PAM and Ab have been reported to decrease in AD CSF (Wand et al 1987;Squitti et al 2006). On the contrary, albumin, which can bind exchangeable copper ion at its amino terminus (Linder and Hazegh-Azam 1996) and is present at the concentration of 4 lM (Aldred et al 1995), might be a reasonable candidate for binding copper in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…PAMmRNAtranscripts were detected in these cells by in situ hybridization histochemistry PAMActivity in CSF In this study, we found that, of the five groups of patients, PAMactivity in the CSF was significantly increased only in the MS group. No group showed decreased PAMactivity, although this study did not include patients with dementia of the Alzheimer type, whose CSFPAMactivity has been shown to be reduced (3). Since the level ofCSF PAMactivity was not influenced by the protein level or the cell count in the CSF, or by the serum level of PAMactivity, it is conceivable that CSF PAMactivity reflects the enzyme activity of the CNS.…”
Section: Discussionmentioning
confidence: 93%
“…If PAMactivity is insufficient, various neurological dysfunctions may occur. Wandet al (3) reported that PAM levels were reduced in the cerebrospinal fluid (CSF) of patients with dementia of the Alzheimer type compared with healthy, age-matched controls. When these neurons are extensively destroyed in some disorders, it could be anticipated that PAM would be released into the CSF.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the fact that several cuproenzymes reveal decreased activity in AD brain tissue. Cytochrome c oxidase (COX) and peptidylglycine alpha amidating monooxygenase have significantly reduced activities in brain and CSF respectively [64][65][66]. Deficiencies in COX levels and activity may be responsible for the deficit in energy metabolism characteristic of AD brain [67,68].…”
Section: Cu Homeostasis In Alzheimer's Disease Brainmentioning
confidence: 99%